Identification of formalin and borax on tuna in Ngemplak market Tulungagung regency - Qurrotu A’yunin Lathifah; Dora Dayu Rahma Turista; Ludfiana Azizah; Ahmad Erfan Khulaifi (Medical Laboratory Analysis and Sciences Journal, 2019)
Misuse of formalin and borax is still common, including processing and preserving fish. Therefore, this study aims to identify the presence of formalin and borax in tuna on the market Ngemplak, Tulungagung regency. The samples used in this study were fresh tuna in the Ngemplak market originating from the beaches of Prigi, Sine, Tambakrejo, Popoh and Sidem. The samples were tested qualitatively using the colorimetric method by Schryver reagent for formalin and curcumin paper for borax. The results obtained in this study, from the five tuna samples not detected contained formalin and borax which were marked by no change in color in the test. Tuna sold in the Ngemplak market Tulungagung regency negatively contains formalin and borax, making it safe for consumption. It is hoped that the relevant office will carry out routine checks on the misuse of food additives, especially preservatives circulating in the community and the public should always be careful in choosing safe food.